Ternstroemia kobuskii (Pentaphylacaceae), a new canopy tree species to the Brazilian Atlantic Rainforest - Vieira, Jaqueline Alves [UNESP]; Monzoli, João Victor Longhi [UNESP]; Sampaio, Daniela [UNESP] (FapUNIFESP (SciELO), 2024)
Here, we describe a new species of Ternstroemia (Pentaphylacaceae) from the Brazilian Atlantic Rainforest. Ternstroemia kobuskii differs from other extra-Amazonian species of Ternstroemia due to its height, reaching up to 28 meters, corresponding to a canopy tree, and its fruit, which is circumscissile-dehiscent, 3-locular, with 1–2 seeds per locule. Ternstroemia kobuski populations are limited to few specimens and a small number of localities in high-altitude slope forests, such as Santa Teresa (state of Espírito Santo) and Tabuleiro Forests, such as Una, and Belmonte (state of Bahia).
Descrevemos, aqui, uma nova espécie de Ternstroemia (Pentaphylacaceae) da Mata Atlântica brasileira
Keywords: Neotropical Region; South America; taxonomy; Ternstroemiaceae